O Corpo do grupo corpo: os movimentos das obras Benguelê, Lecuona e Onqotô - Silva, Thays Anyelle Macedo da (2013)
In this research, we invite to reflection by a phenomenological gaze on the body, through the description of some works of contemporary Brazilian dance company Grupo Corpo. This Company was chosen intentionally to give us elements in their creations to interrogate the understanding of the body and sensitive. Thus, as we launch issues in this dissertation: that body dance in Grupo Corpo? And as we can see, a phenomenological approach, an understanding of the body and sensitive works in that company? Building on this, the works are to be questioned Benguelê (1998/2003), Lecuona (2004) and Onqotô (2005). It is intended, through these works, coreological approaching the discourse of philosophical discourse and give movement to phenomenological thought of Maurice Merleau-Ponty, in special the sensitive, flesh of the body, the investment in the sensory world as a merger, calling the know body and its power to take chances, to incorporate the world, language, culture, create and choose. Thus, these openings is where thought enters this research. This consistency, we used the phenomenological attitude of Maurice Merleau-Ponty as a methodological approach, since in their study the philosopher takes a look expressive on the body, forming a sensitive language that is expressed in the movements, which deepens the arguments of the Phenomenology a new arrangement for knowledge as a result of our experience in the lived world. The reflections presented here aim to take us to the amazement, the unthinking, whom many still impose epistemological challenges, including understanding the body of knowledge and sensitive